Three-dimensional topographic and gravity anomaly maps in the vicinity of Mizuho Plateau, East Antarctica - Toshiyasu Nagao; Masaru Awara; Katsutada Kaminuma (National Institute of Polar Research, 1991)
A re-compilation of gravity data around Syowa Station, East Antarctica (68°-78°S, 25°-55°E) was made, to present three-dimensional contour maps of gravity anomalies. Ice sheet and bedrock topography contour maps were also obtained. Gravity values calculated by Potsdam System are unified to IGSN71 System, and accuracy of gravity values was evaluated. In Mizuho Plateau, some gravity anomalies had been calculated by the geoid height, and others by the height from WGS-72 ellipsoids. Therefore, to remove this confusion, we recalculated all of gravity anomalies using the geoid height. The results are as follows : 1) An accuracy of gravity value determination is less than 3 mgal. 2) An accuracy of free air anomaly is about 10mgal. 3) The result of bedrock elevation determination observed with radio echo sounding and that estimated from gravity data show a rather good coincidence in general. However, a detailed comparison reveals many local discrepancies between the two results. Accurate determination of bedrock topography is one of the most significant items for understanding the region.